Lower Performance in the Six-Minute Walk Test in Obese Youth With Cardiometabolic Risk Clustering - Valerio, Giuliana; Licenziati, Maria Rosaria; Tortorelli, Paola; Calandriello, Lidia Federica; Alicante, Paola; Scalfi, Luca (Frontiers in Endocrinology, 2018)
Background: Physical fitness is an important index of health. Our aim was to assess whether cardiorespiratory and/or musculoskeletal components of physical fitness were associated with cardiometabolic risk clustering in obese youth, using adapted and validated field tests. Methods: We evaluated 252 children and adolescents (132 males, 120 females), mean age 10.9 ± 1.9 years with primary obesity. All subjects performed the six-minute walk test (6MWT) for assessing aerobic fitness, the standing broad jump, and the 30 s-chair stand tests for lower-body muscular strength, and the handgrip test for upper body isometric strength. Cardiometabolic risk (CMR) clustering was defined as having two or more of the following risk factors: high SBP and/or DBP, impaired fasting glucose, high triglycerides (TGs), and low HDL-Cholesterol. Results: CMR clustering was found in 44 (17.5%) obese youth. Youth with CMR clustering had a lower cardiorespiratory fitness, as assessed by 6MWT, compared to those without CMR clustering. On the contrary, no difference was found with respect to musculoskeletal fitness. The six-minute walk (6MW) distance was negatively associated with sedentary time, controlling for age and height. CMR factors clustering was significantly associated with BMI standard deviation score (SDS) and negatively with 6MW distance: for each 10-m increase in the 6MW distance, a reduction of about 9% in the prevalence of CMR clustering was expected. Conclusions: A lower performance in the 6MWT may be considered as an additional trait of CMR clustering in obese youth. The 6MWT may represent a valuable, simple and low cost test to estimate the cardiorespiratory fitness in youth with obesity.